Fly ash-TiO2 nanocomposite material for multi-pollutants wastewater treatment. (1st March 2015) - Visa, Maria; Andronic, Luminita; Duta, Anca
Abstract: This paper reports on the synthesis, characterization and adsorption properties of a novel nano-composite obtained using the hydrothermal method applied to a fly ash-TiO2 slurry and hexadecyltrimethyl-ammonium bromide, as surface controlling agent. The new adsorbent was investigated in terms of crystallinity (XRD), surface properties (AFM, SEM, and porosity and BET surface) and surface chemistry (EDX, FTIR). The nanocomposite's properties were sequentially tested in adsorption and photocatalysis processes applied to multi-pollutant synthetic wastewaters loaded with copper cations and two industrial dyes: the acid dye Bemacid Blau and the reactive dye Bemacid Rot; the nano-composite substrate allowed reaching high removal efficiencies, above 90%, both in adsorption and in photodegradation experiments, in optimised conditions. Graphical abstract: Highlights: A novel substrate FAA-DCS is obtained by hydrothermal synthesis. The composite type structure has specific surface ten times higher than fly ash. Simultaneous removal of three pollutants reaches efficiencies above 90%. The adsorption on FAA-DCS represents a preliminary step in photocatalysis of the dye. Kinetic investigations show fast adsorption of the dye on the new composite.